(untitled) (Revista Electrónica REDINE, 2020)
The purpose of this research is to: Interpret the meaning of the Canaima Educational Tool from the pedagogical perspective of Primary Education Teachers of the EB “Manuel Cedeño”, Peña Municipality, Yaracuy state, for which the following purposes were established: (a) Explore the reasons that lead to the use of the Canaima Educative tool from the pedagogical perspective of primary school teachers. (b) Describe the factors that influence the pedagogical use of the Canaima Educative tool by primary school teachers; and (c) Unveil the use of the Canaima Educative tool from the pedagogical perspective of Primary Education teachers. Likewise, this proposal was methodologically framed in the interpretive paradigm, with a qualitative approach, under the phenomenological method supported by hermeneutics, and the research line Information and Communication Technology. Contributing to generate new contributions by interpreting the pedagogical use of the Canaima Educative tool, under an innovative and constructivist conception that is in accordance with the new educational trends and environment in which the student operates